The Fruit Hull of Gleditsia sinensis Enhances the Anti-Tumor Effect of cis-Diammine Dichloridoplatinum II (Cisplatin). (18th September 2016) - Kim, Kyun Ha; Han, Chang-Woo; Yoon, Seong Hoon; Kim, Yun Seong; Kim, Jong-In; Joo, Myungsoo; Choi, Jun-Yong
Abstract : Lung cancer has substantial mortality worldwide, and chemotherapy is a routine regimen for the treatment of patients with lung cancer, despite undesirable effects such as drug resistance and chemotoxicity. Here, given a possible antitumor effect of the fruit hull of Gleditsia sinensis (FGS), we tested whether FGS enhances the effectiveness of cis -diammine dichloridoplatinum (II) (CDDP), a chemotherapeutic drug. We found that CDDP, when administered with FGS, significantly decreased the viability and increased the apoptosis and cell cycle arrest of Lewis lung carcinoma (LLC) cells, which were associated with the increase of p21 and decreases of cyclin D1 and CDK4. Concordantly, when combined with FGS, CDDP significantly reduced the volume and weight of tumors derived from LLC subcutaneously injected into C57BL/6 mice, with concomitant increases of phosphor-p53 and p21 in tumor tissue. Together, these results show that FGS could enhance the antitumor activity of CDDP, suggesting that FGS can be used as a complementary measure to enhance the efficacy of a chemotherapeutic agent such as CDDP.